2010
DOI: 10.1074/jbc.m110.123422
|View full text |Cite
|
Sign up to set email alerts
|

Neobiosynthesis of Glycosphingolipids by Plasma Membrane-associated Glycosyltransferases*

Abstract: Gangliosides, complex glycosphingolipids containing sialic acids, are synthesized in the endoplasmic reticulum and in the Golgi complex. These neobiosynthesized gangliosides move via vesicular transport to the plasma membrane, becoming components of the external leaflet. Gangliosides can undergo endocytosis followed by recycling to the cell surface or sorting to the Golgi complex or lysosomes for remodeling and catabolism. Recently, glycosphingolipid catabolic enzymes (glycohydrolases) have been found to be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
4
38
0
Order By: Relevance
“…Sial-T2ϩ Cells-We recently demonstrated by biochemical approaches, combined with confocal microscopy and flow cytometric analysis, the expression and cis-activity of ectoSial-T2 at the cell surface of epithelial and melanoma cells (14). In this study, these results were further confirmed and validated by using the very sensitive and specific ELISA procedure.…”
Section: Gm3 Expressed At the Cell Surface Of Cho-k1 Wt Cells Is Catasupporting
confidence: 61%
See 4 more Smart Citations
“…Sial-T2ϩ Cells-We recently demonstrated by biochemical approaches, combined with confocal microscopy and flow cytometric analysis, the expression and cis-activity of ectoSial-T2 at the cell surface of epithelial and melanoma cells (14). In this study, these results were further confirmed and validated by using the very sensitive and specific ELISA procedure.…”
Section: Gm3 Expressed At the Cell Surface Of Cho-k1 Wt Cells Is Catasupporting
confidence: 61%
“…Sial-T2ϩ Cells Sialylates GM3 Ganglioside Immobilized onto a Solid Surface-Many reports have described the significance of the regulation of the glycolipid metabolism at the plasma membrane (13,14,17,18). However, the possibility that ecto-Sial-T2 may catalyze the conversion of GM3, belonging to the surface of neighboring cells, to the ganglioside GD3 has not yet been described.…”
Section: Ecto-sial-t2 From Cho-k1mentioning
confidence: 99%
See 3 more Smart Citations